2020
DOI: 10.1111/sode.12498
|View full text |Cite
|
Sign up to set email alerts
|

Self‐regulated behavior and parent‐child co‐regulation are associated with young children's physiological response to receiving critical adult feedback

Abstract: Using piecewise growth curve trajectory modeling, we investigated kindergartners' physiological responses to receiving critical feedback from an adult during a laboratory drawing task. Further, we tested how children's independent self-regulated behavior, as well as the quality of parentchild co-regulation, related to physiological reactivity to and recovery from this challenge. We used respiratory sinus arrhythmia (RSA) to measure parasympathetic nervous system activity. Participants were 96 children (M age =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 59 publications
0
8
0
2
Order By: Relevance
“…Positive behavioral co-regulation reflects the extent to which parent and child display positive, reciprocal, and harmonious patterns of behavior during shared dyadic interactions, and is uniquely important for child adjustment (MacPhee et al, 2015). Young children from dyads that show more positive behavioral co-regulation exhibit more self-regulated behavior (Bardack, Herbers, & Obradović, 2017;Lunkenheimer, Hamby, Lobo, Cole, & Olson, 2020;Scholtes, Lyons, & Skowron, 2021;Suveg et al, 2016), and respond with greater RSA withdrawal during individualized laboratory challenges (Armstrong-Carter, Sulik, & Obradović, 2021). However, it remains unclear whether positive behavioral co-regulation is related to parentchild physiological synchrony.…”
Section: Behavioral Correlates Of Physiological Synchronymentioning
confidence: 99%
“…Positive behavioral co-regulation reflects the extent to which parent and child display positive, reciprocal, and harmonious patterns of behavior during shared dyadic interactions, and is uniquely important for child adjustment (MacPhee et al, 2015). Young children from dyads that show more positive behavioral co-regulation exhibit more self-regulated behavior (Bardack, Herbers, & Obradović, 2017;Lunkenheimer, Hamby, Lobo, Cole, & Olson, 2020;Scholtes, Lyons, & Skowron, 2021;Suveg et al, 2016), and respond with greater RSA withdrawal during individualized laboratory challenges (Armstrong-Carter, Sulik, & Obradović, 2021). However, it remains unclear whether positive behavioral co-regulation is related to parentchild physiological synchrony.…”
Section: Behavioral Correlates Of Physiological Synchronymentioning
confidence: 99%
“…Developmental psychophysiology researchers have emphasized the importance of studying physiological recovery and identifying factors that explain different recovery trajectories in children (Burt & Obradović, 2013;Kahle et al, 2018;Obradović, 2012Obradović, , 2016. Descriptive developmental research has shown that children's cognitive, behavioral, and emotional self-regulation skills are significantly linked to their physiological recovery following a laboratory task (Armstrong-Carter et al, 2020;Finch & Obradović, 2017;Santucci et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Developmental psychophysiology researchers have emphasized the importance of studying physiological recovery and identifying factors that explain different recovery trajectories in children (Burt & Obradović, 2013; Kahle et al., 2018; Obradović, 2012, 2016). Descriptive developmental research has shown that children's cognitive, behavioral, and emotional self‐regulation skills are significantly linked to their physiological recovery following a laboratory task (Armstrong‐Carter et al., 2020; Finch & Obradović, 2017; Santucci et al., 2008). Determining whether experimentally induced regulation of breathing has a causal effect on children's physiological recovery following a cognitively or emotionally challenging task is a critical next step in translating this work into caregiving and educational practices that can promote children's well‐being.…”
Section: Discussionmentioning
confidence: 99%
“…According to the transactional model of self-regulatory skill development (Sameroff, 2010), children's skills develop in a careful balance between their own self-regulation and "other"-regulation (resulting in a dynamic process of "co-regulation"; e.g., Armstrong-Carter et al, 2021). Early in life, infants rely on other-regulation for nearly every- Stammbach et al, 2014;Hendry et al, 2016).…”
Section: 1mentioning
confidence: 99%
“…According to the transactional model of self‐regulatory skill development (Sameroff, 2010), children's skills develop in a careful balance between their own self‐regulation and “other”‐regulation (resulting in a dynamic process of “co‐regulation”; e.g., Armstrong‐Carter et al., 2021). Early in life, infants rely on other‐regulation for nearly everything: Caregivers do what is necessary to keep the child safe, warm, and fed, as children are unable to do it themselves.…”
Section: Introductionmentioning
confidence: 99%